The Attraction Of The Menu Set At Mari Merangkai Bunga Seroja Restaurant In Bandung - Fajri, Ilham; Wibawa, Idham Sakti; Karnita, Ita (Universitas Indonesia Membangun (Inaba), 2025)
This study aims to determine the attractiveness of set menus at Mari Merangkai Bunga Seroja restaurant in Bandung. In this study, a quantitative descriptive method with a Likert scale was used, involving 96 respondents as samples. The questionnaire distributed to respondents focused on several aspects of set menu attractiveness, including food quality, price, theme or concept, and overall dining experience. The data obtained were analyzed using a Likert scale to describe the level of attractiveness of the set menus provided by the restaurant. The results showed that most respondents gave positive ratings to the attractiveness of the set menus at Mari Merangkai Bunga Seroja restaurant. Food quality and price were the main factors influencing the attractiveness of the set menus, with most respondents feeling satisfied with the prices offered in relation to the quality and taste of the food. Additionally, the attractive presentation and the restaurant's ambiance also contributed to a positive experience with the set menu offered. Based on these findings, Mari Merangkai Bunga Seroja restaurant is encouraged to maintain and enhance the appeal of their set menu to attract more visitors